Practice of hysteroscopy at the Hospital for Applied Research, Endoscopic Surgery, and Human Reproduction, Yaounde Cameroon - Noa Nduoa, Claude Cyrille; Ntsama Metogo, Junie Annick; Ngono, Xavier Ayissi; Mbeng, Selma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: This study was done to describe the practice of hysteroscopy at the Hospital Centre for Applied Research, Endoscopy, Surgery and Human Reproduction (CRACERH). Methods: It was a descriptive retrospective cross section study between January 2015 to December 2020.All patients who underwent either an operative or diagnostic hysteroscopy during the study period were included. Data was collected from postoperative reports, patients medical files and registered on a pre-established data collection form. The indications for surgery, the operative findings were also noted. Any unexpected incident during the procedure or postoperative was considered a complication. Results: During the study period, 1876 patients underwent a surgical procedure, of which 287 had a hysteroscopy making a percentage of 15.29%. The average age of the 287 patients was 39.38±6.36 years. Majority of the patients were still menstruating with only 3.8% (n=11/287) were menopaused. The most frequent pathology found during diagnostic hysteroscopy was the polyp with a ratio of 65.6%, and uterine myoma with a ratio of 43.7% (87). Conclusions: Our study highlights the fact that hysteroscopy occupies a preponderant role in the diagnosis of intra uterine pathology especially in the context of infertility.